E-Counseling System Mental Health to Increase Self Hope During the Covid-19 Pandemic - Sukma Rahmawati; Eko Purwanto (LPPM Universitas Duta Bangsa Surakarta, 2021)
Indonesia since 2020 has implemented the Work From Home to break the chain of transmission of Covid-19. facing a pandemic because the Covid-19 virus emerged from Wuhan, China. To meet the needs, the constant saturation, and the anxiety that comes from being too afraid of this virus. In fact, mental health is very important for work or even more productive activities, because if we are mentally and mentally healthy, physically we can follow activities properly. So maintaining mental health is very important in order to be able to face the pandemic atmosphere and still have a purpose in life. It doesn't just stop there, the pandemic also attacks everyone mentally, economic instability causes people to work harder and be depressed. Therefore, this paper is written to propose the idea of ​​a mental health consultation system as a mediator to increase life expectancy. Economic instability causes people to work harder and pressured to make ends meet, the boredom that continues to be felt, and the anxiety that is present from being too afraid of the virus. The method used in this paper is the literature study method and the existence of a design system called the prototyping method. Literature study is carried out by collecting relevant information on topics that are the object of research from books, scientific papers, theses, dissertations, and journals, while prototypes are the development stage before heading to actual large / scale production. The result that will be obtained is enough feeling to be an entertainer and a solution for everyone who is already at a point of hopelessness or who just wants to get answers to his anxiety so far, in order to increase life expectancy and strengthen mentally after counseling.